The fundamentals of Drawing still life : a practical and inspirational course - Barber, Barrington (London Arcturus Publishing Limited, 2022)
"From the fundamental techniques of practising shapes and shading to choosing the right art medium to how to convey texture and substance, Barrington Barber guides the would-be artist through the process of creating first-class still life works of art. With approximately 200 specially drawn images, Drawing Still Life is the ultimate guide for those wishing to improve their skills in this classic art form."--
Includes index.
Keywords: Still-life in art -- Technique; Pencil drawing -- Technique; Drawing -- Technique